Men's and women's spheres among couples from Maniitsoq (Greenland) - Williamson, Karla (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2006)
AbstractThis paper looks at gender relations and presents original findings of an empirical study among the Kalaallit (Greenland Inuit) of Maniitsoq (southwest Greenland). The focus of the study was to figure out what gender roles look like in Kalaallit eyes. Seven couples were interviewed about what work entails in different contexts. All the women interviewed have a job, and they describe their activities in their own homes. They are involved in social activities (including those related to the Church) much more so than their husbands, and have more control on the values involved in raising their children. Five of the husbands had a job but only four were involved in “recreational” hunting. Husbands are less inclined in Church matters but find spiritual connection while out on the sea and hunting. But these Kalaallit men are becoming more socially isolated. The paper ends with the presentation of three models of couplehood in Maniitsoq: traditional; detached; and reversed.